2022
DOI: 10.1002/mnfr.202100772
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Gut Microbiota and Host Metabolism with Dendrobium officinale Dietary Fiber to Prevent Obesity and Improve Glucose Homeostasis in Diet‐Induced Obese Mice

Abstract: Scope: Obesity is becoming a major public health problem due to excess dietary fat intake. Dendrobium officinale (D. officinale) is a medicine food homology plant and exerts multiple health-promoting effects. However, its antiobesity effects and the potential mechanisms remain unclear. Methods and results: High-fat diet (HFD)-fed mice are administered D. officinale dietary fiber (DODF) daily by gavage for 11 weeks. The results show that treatment with DODF alleviates obesity, liver steatosis, inflammation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…Previous studies reported that the obese and NAFLD subjects always had a higher abundance of Firmicutes . Gln supplementation decreased the abundance of Firmicutes , Muribaculum , and Lachnospiraceae_NK4A136_group of obese mice as previously described, while HFD increased the abundance of Lachnospiraceae_UCG-006 . These results demonstrated that Gln supplementation suppresses lipotoxicity induced by the HFD, restoring the healthy microbiota composition.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies reported that the obese and NAFLD subjects always had a higher abundance of Firmicutes . Gln supplementation decreased the abundance of Firmicutes , Muribaculum , and Lachnospiraceae_NK4A136_group of obese mice as previously described, while HFD increased the abundance of Lachnospiraceae_UCG-006 . These results demonstrated that Gln supplementation suppresses lipotoxicity induced by the HFD, restoring the healthy microbiota composition.…”
Section: Discussionsupporting
confidence: 81%
“…is inversely associated with metabolic diseases such as obesity and diabete. 40 Akkermansia spp. supplementation by gavage in obese mice significantly reversed high-fat diet-induced insulin resistance, metabolic endotoxemia, and improved fat accumulation and fasting hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of possible biological mechanisms might explain the positive associations between the consumption of SSBs and ASBs and risk of T2D and cardiometabolic disease. Consumption of SSBs and ASBs is associated with the risk of obesity, which is an independent risk factor for cardiometabolic disease (84,(89)(90)(91)(92). For SSBs, another independent factor may arise from the large amount of rapidly absorbable carbohydrates, such as fructose added to SSBs.…”
Section: Discussionmentioning
confidence: 99%